Presumed guilty [large type] - Turow, Scott (Grand Central Publishing, Hachette Book Group, 2025)
"Rusty is a retired judge attempting a third act in life with a loving soon-to-be wife, Bea, with whom he shares both a restful home on an idyllic lake in the rural Midwest and a plaintive hope that this marriage will be his best, and his last. But the peace that's taken Rusty so long to find evaporates when Bea's young adult son, Aaron, living under their supervision while on probation for drug possession, disappears. If Aaron doesn't return soon, he will be sent back to jail. Aaron eventually turns up with a vague story about a camping trip with his troubled girlfriend, Mae, that ended in a fight and a long hitchhike home. Days later, when she still hasn't returned, suspicion falls on Aaron, and when Mae is subsequently discovered dead, Aaron is arrested and set for trial on charges of first-degree murder. Faced with few choices and even fewer hopes, Bea begs Rusty to return to court one last time, to defend her son and to save their last best hope for happiness. For Rusty, the question is not whether to defend Aaron, or whether the boy is innocent--it's whether the system to which he has devoted his life can ever provide true justice for those who are presumed guilty"--